SPECTRUM OF FINDINGS IN PATIENTS PRESENTING FOR UPPER GASTROINTESTINAL ENDOSCOPY AT A TERTIARY CARE HOSPITAL AND THE INFLUENCE OF AGE AND GENDER - Hassan, Fayyaz; Ahmad, Khalil; Ayaz, Saeed Bin; Khalil, Heyyan Bin (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the spectrum of findings in patients presenting for upper gastrointestinal (UGI) endoscopy and investigate role of age and gender.Study Design: Cross-sectional study.Place and Duration of Study: Department of Gastroenterology & Internal Medicine, Combined Military Hospital Kharian, from Jul 2017 to Mar 2019.Methodology: The data regarding 638 consecutive patients who underwent upper gastrointestinal endoscopy in the department were collected from the computer-based database and patients were stratified into two groups according to their age: ≤50 and >50 years.Results: The mean age was 50.2 ± 17.4 (range: 7-100) years. There were 431 males and 207 females. The commonest presenting complaint was decompensated chronic liver disease (CLD) 162 (25.4%). The upper gastrointestinal endoscopy was normal in 306 (48%) and abnormal in 332 (52%) patients. The commonest abnormality seen on upper gastrointestinal endoscopy was esophageal varices seen in 167 (26.2%) followed by non-specific gastropathy, and hiatal hernia seen in 28 (4.4%) and 21 (3.3%) patients respectively. No significant differences were observed among males and females for a positive upper gastrointestinal endoscopy. Significantly large number of patients of age >50 years had an abnormal upper gastrointestinal endoscopy (p